Pengaruh Model Pembelajaran Discovery Learning Berbantuan Media Video terhadap Hasil Belajar IPAS Siswa - Renta Ria Br Manalu; Regina Sipayung; Patri Janson Silaban; Antonius Remigius Abi; Irmina Pinem (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aimed to determine the effect of the Discovery Learning model assisted by instructional video media on the science and social studies (IPAS) learning outcomes of fourth-grade students at UPT SD Negeri 060883 Medan Petisah in the 2025/2026 academic year. This research employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest–Posttest Design. The sample consisted of 30 fourth-grade students selected through a saturated sampling technique. The research instruments included a 20-item multiple-choice achievement test and a student response questionnaire. Data were analyzed using normality, Pearson correlation, coefficient of determination, and t-tests with IBM SPSS Statistics version 22. The results revealed that the mean pretest score increased from 50.50 to 85.13 on the posttest. The correlation analysis yielded r = 0.841, indicating a very strong relationship, while the coefficient of determination was 70.7%. The hypothesis test showed tcount = 8.215 > ttable = 2.048 with a significance value of 0.000 < 0.05. Therefore, the Discovery Learning model assisted by instructional video media significantly improved students' IPAS learning outcomes and effectively supported active learning in the implementation of the Merdeka Curriculum.